2002
DOI: 10.1142/s0192415x02000338
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Garlic Components Diallyl Sulfide and Diallyl Disulfide on Arylamine N-Acetyltransferase Activity and 2-Aminofluorene-DNA Adducts in Human Promyelocytic Leukemia Cells

Abstract: Two components of garlic, diallyl sulfide (DAS) and diallyl disulfide (DADS), inhibited arylamine N-acetyltransferase (NAT) activity and 2-aminofluorene-DNA adduct in human promyelocytic leukemia cells (HL-60). The NAT activity was measured by high performance liquid chromatography assaying for amounts of N-acetyl-2-aminofluorene (2-AAF) and remaining 2-aminofluorene (2-AF). Cellular cytosols and intact cell suspensions were assayed. The inhibition of NAT activity and 2-AF-DNA adduct formation in human leukemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…A study has been reported that the garlic components DAS and DADS are the effective inhibitors of bladder and colon cancer progression. The in-vitro study has shown that the compounds can inhibit the arylamine N-acetyltransferase (NAT) activity to produce carcinogens from foreign substances, cell growth, and DNA adduct formation of bladder and colon tumour cells in a dose-dependent manner [ 34 , 64 ]. Another garlic compound called allicin was reported to induce the p53 mediated autophagic cell death in Hep G2 liver cancer cells.…”
Section: Biological Activities Of Sulfur Compounds From mentioning
confidence: 99%
“…A study has been reported that the garlic components DAS and DADS are the effective inhibitors of bladder and colon cancer progression. The in-vitro study has shown that the compounds can inhibit the arylamine N-acetyltransferase (NAT) activity to produce carcinogens from foreign substances, cell growth, and DNA adduct formation of bladder and colon tumour cells in a dose-dependent manner [ 34 , 64 ]. Another garlic compound called allicin was reported to induce the p53 mediated autophagic cell death in Hep G2 liver cancer cells.…”
Section: Biological Activities Of Sulfur Compounds From mentioning
confidence: 99%
“…Caffeic acid, esculetin, quercetin, kaemferol and genistein inhibited NAT1 whereas scopuletin and coumarin inhibited NAT2 88 . Chen et al 89 and Lin et al 90 described the effect of diallyl sulfide (DAS) and diallyl disulfide (DADS), major components of garlic, on NAT activity in human colon tumor cells and human promyelocytic leukemia cells. These studies demonstrated that DAS and DADS markedly inhibited NAT activity in these cells and would thus assist the organism in defense against cancer.…”
Section: Substrates Inhibitors and Inductors Of Natsmentioning
confidence: 99%
“…DADS inhibited 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP)-induced mammary cancer in rats by significantly lowering both the ductal carcinoma incidence and multiplicity of total tumors [17]. DADS has demonstrated anticarcinogenic properties in numerous human cancer cell lines including HepG2 hepatoma [18], HL-60 leukemia [19], non-small cell lung cancer [20], SH-SY5Y neuroblastoma [21], MCF-7 breast cancer [22], as well as Caco-2 and HT-29 colon tumor cells [23, 24]. The role of DADS in preventing carcinogenesis in normal cells has not been fully elucidated so further research is needed to evaluate its capacity for inhibiting early stage cancer initiation in non-neoplastic cells.…”
Section: Introductionmentioning
confidence: 99%